Building-façade integrated solar thermal collectors: Energy-economic performance and indoor comfort simulation model of a water based prototype for heating, cooling, and DHW production. (July 2019) - Buonomano, A.; Forzano, C.; Kalogirou, S.A.; Palombo, A.
Abstract: This paper presents the design and the thermodynamic analysis of a new prototype of flat-plate solar thermal collector, suitable for building integration, using water as working fluid. The main novelty of the proposed solar thermal collector is the use of cheap materials and simple design solutions, taken into account with the aim to reduce the manufacturing and installation costs towards the improvement of the market penetration of this technology in the near-term future. The collector is suitable for domestic hot water production and for space heating and cooling, achieved through the use of adsorption chillers. A suitable dynamic simulation model for the system energy, comfort, economic, and environmental performance assessment is developed by taking into account both active and passive effects related to the building integration of the solar collector. The developed simulation model, implemented in a suitable MatLab computer tool, is experimentally validated; the main results of the validation process are discussed in this paper. Moreover, in order to show the potential of the presented building integrated collector prototype and of the related simulation tool, a suitable case study is developed. It refers to a residential unit of a multi-floor building where the prototype collectors are integrated on the South façade. Simulations are carried out for 2 building envelope weights and 9 different weather zones. Interesting outcomes from the energy, economic, environmental, and comfort point of views are obtained. Highlights: Dynamic modelling of building integrated solar thermal collectors. Experimental validation of the developed simulation model. Solar collectors are integrated in the South façades of a residential building. Active/passive effects on the building envelope are assessed for different climates. High energy demand reductions for heating, cooling and DHW production is obtained.